MATHEMATICAL SIMULATION OF ELECTROMAGNETIC PROCESSES IN CURRENT SENSOR FOR ELECTRICAL EQUIPMENT PROTECTION SYSTEMS - Mikhail R. Vinokurov; Anatoly A. Lavrentyev; Maxim M. Tolstunov (Advanced Engineering Research)
The linear solution to the electromagnetic analysis, when the field is created by the sinusoidal current captured with the ferromagnetic conductive ring, is presented. The given analytical investigations are confirmed experimentally. The results permit to specify the characteristics of the ferromagnetic conducting environment with a reasonable degree of accuracy.